N,N ',N '-trisubstituted thiourea as a novel sulfur source for the synthesis of Mn-doped ZnS QDs - Kadeřávková, Anastasia; Loghina, Liudmila; Chylii, Maksym; Šlang, Stanislav; Plaček, Patrik; Frumarová, Božena; Vlček, Miroslav (Elsevier Science SA, 2020)
Doping of semiconductor quantum dots (QDs) by transition metals (such as Mn, Cu, Ni, etc.) is a great technique to impact the optical and structural properties of the host materials. The introduction of a small amount of impurity into the host semiconductor matrix leads to the shift of PL emission due to the change in the recombination process. The new emission pathways created by dopant influence the photoluminescence intensity, Stokes shift, lifetime and stability of QDs. Mn-doped ZnS QDs (1-15 mol. %) have been synthesized by the effective low-cost and nontoxic hot-injection method. N-phenylmorpholine-4-carbothioamide has been successfully applied as a novel source of sulfur in the synthesis of Mn-doped ZnS QDs. X-ray diffraction (XRD), scanning transmission electron microscopy (STEM) and infrared (IR) spectroscopy were used for the characterization of morphology and structure of synthesized Mn-doped ZnS QDs. Our materials exhibit strong photoluminescence yellow-orange emission with a photoluminescence quantum yield (PL QY) of 41%. All Mn-doped ZnS QDs have a face-centered cubic structure with a mean crystalline size of 3.8-5.1 nm. Additionally, this synthetic approach enables the synthesis of Mn-doped ZnS QDs with tunable band gaps between similar to 3.5 eV and 3.60 eV.
N,N ',N '-trisubstituovaná thiomočovina jako nový zdroj síry pro syntézu Mn-dopovaných kvantových teček ZnS
Keywords: quantum dots; substituted thioureas; semiconductors; kvantové tečky; substituované thiomočoviny; polovodiče